Supporting Trans and Non-Binary People – Best Practice Guidance for Health & Wellbeing Practitioners – a Bristol-Based Project Co-Produced by Mental Health Specialists, a Charitable Organisation Stand Against Racism & Inequality (SARI), Local LGBTQ+ Champions and the Local Trans and Non-Binary Community - Daniel Hodgson; Alex Raikes (BJPsych Open)
Aims: Mental health support for trans and non-binary people has been under scrutiny for many years. Trans and non-binary people often present to mental health services with co-morbid mental health difficulties. Medical practitioners often report a lack of training and understanding. GPs, psychiatrists and allied health professional frequently request more information to help educate and inform their practice and to support them in offering the best care for their patients and their families and carers.